Ekologi Integral dalam Terang Dokumen Laudato Si: Menjawab Tantangan Kerusakan Alam di Kabupaten Ketapang - Heribertus Kurnia Taman (Borneo Review, 2025)
The technocratic paradigm and anthropocentric worldview in modern society have driven the intensive exploitation of natural resources, resulting in significant negative impacts on environmental sustainability. This study highlights the case of Ketapang Regency in West Kalimantan, which has experienced severe ecological degradation due to massive deforestation driven by palm oil plantation expansion, mining activities, and illegal exploitation. The aim of this research is to examine the relevance of the integral ecology approach as proposed by Pope Francis in the encyclical Laudato Si’ as a strategy for mitigating environmental damage at the local level. Using a literature review method that draws from Church documents, ecological literature, and contextual data from Ketapang, the study finds that the integral ecology framework—encompassing environmental, social, economic, and cultural dimensions—offers a sustainable, just, and participatory solution, particularly in protecting the rights and roles of indigenous communities. The findings show that integral ecology is not merely a conceptual framework but also an ethical and spiritual foundation that can foster ecological awareness among communities and support more holistic environmental policies. This study is expected to contribute to the reformulation of sustainable regional development policies and strengthen the role of religious communities in ecological education and grassroots action.